Gender differences in the subjective well-being of older adult learners in China - Shi, Xiaowei; Li, Yuan; Sun, Lixin; Yu, Yong; Zhou, Shiyu (Frontiers in Psychology, 2022)
The trend of feminization of the aging population” and “feminization of the senior population in China is accelerating, and the differences in the subjective well-being of older adults are becoming more and more obvious. This study combines gender theory with gender differences as an entry point, based on 436 survey data, and examines effects and differences between learning engagement on the subjective well-being of older Chinese learners by gender. The study found the following: learning can enhance the subjective well-being of older people; there were significant differences in the subjective well-being of older learners by gender in two dimensions, namely, physical and mental health experience and adaptation satisfaction experience; and the positive effect of learning engagement on subjective well-being of female older adults was more pronounced and thus had a stronger effect on their subjective well-being. In addition, the gender equality of older adults’ learning participation and gender differences in learning needs are further explored based on the gender theory perspective, and this gives suggestions for enhancing older learners’ subjective well-being.